Fish sauce from two species of unexploited deep sea fish Peristedion adeni and Peristedion weberi - Shenoy, A.V., Lekshmy Nair, A., Prabhu, P.V. and (Fishery Technology, 2021)
Two species of unexploited deep sea fish Peristedion adeni and Peristedion weberi caught from the Exclusive Economic Zone of India were subjected to fermentation at ambient temperature (30 Â± 2Â°C) in the presence of salt in 4:1 ratio. Periodical analysis of the fermented product was carried out up to one year. The sauces had brownish yellow colour and conformed to special grade of the standards prescribed by the Food and Drug Administration. Further solubilization of protein after 9 month's maturation was not appreciable.